دور البروموكريبتين في إحداث الإباضة لدى مريضات فرط برولاكتين الدم - سلمان, صفاء; عابدين, بسام; العلي, محمد (Latakia University Journal -Medical Sciences Series, 2019)
أجريت الدراسة في قسم التوليد وأمراض النساء - مشفى الأسد الجامعي – اللاذقية – سوريا, وامتدت من تاريخ 1/1/2003 وحتى 31/6/2004 وضمت 65 مريضة بين عمر 18 – 40 سنة وكانت نتائج الدراسة على النحو التالي : عدد مريضات فرط برولاكتين الدم ضمن الفئة العمرية من 26-35 سنة 39 مريضة (60%). عدد مريضات فرط برولاكتين الدم عند السيدات اللواتي حملن من قبل 44 مريضة (67.69%). عدد مريضات ثر الحليب 53 مريضة, كان برولاكتين الدم مرتفعاً لدى 26 مريضة منهن (49,06%). عدد مريضات فرط برولاكتين الدم 38 مريضة, عانت 26 مريضة من ثر الحليب (68,24%). استخدم الإيكو المهبلي ومخطط الحرارة الأساسي في تحري الإباضة. عدد المريضات اللواتي شخص لديهن إباضة ولم يحتجن إلى المعالجة بالبروموكريبتين 27 مريضة (41.54%). عدد المريضات اللواتي لم يكن لديهن إباضة واحتجن للمعالجة بالبروموكريبتين 38 مريضة(48,46%). تم تطبيق العلاج بالبروموكريبتين [2.5-7.5 ملغ / يوم على ثلاث جرعات] لدى 38 مريضة ولمدة 3 دورات حسب حاجة المريضة مع مراقبة حدوث الإباضة لديهن شهرياً. حدثت الإباضة لدى 30 مريضة (78.95%). وفشلت لدى 8 مريضات (21.05%). عدد الدورات العلاجية بالبروموكريبتين 77 دورة. الآثار الجانبية المشاهدة للبروموكريبتين هي : هبوط ضغط انتصابي 8 مريضات (21.05%) ,غثيان 7 مريضات (18.42%)، إقياء 5 مريضات (13.16%)، صداع 4 مريضات (10.53%)، ألم معدي 6 مريضات (15.59%) . The study was carried out in the Department of Obstetrics and Gynecology at Alassad University Hospital in Lattakia from 1/1/2003 to 31/6/2004. The study included 65 patients between 18 – 40 years and the results were : Number of hyperprolactinemia patients within the age from 26 – 35 years is 39 patients (60%). Number of hyperprolactinemia in ladies who had pregnancy previously is 44 patients (67.69%). Number of galactorrhea patients is 53 ,out of which blood prolactin was high in 26 patients (49,06%) . Number of hyperprolactinemia patients is 38 , out of which 26 patients suffered from galactorrhea (68,24%). We used vaginal ultrasound and basal body temprature in ovulation detection . The number of patients who had ovulation without needing therapy by bromocriptin was 27 (41.54%). The number of patients who did not have ovulation and who needed therapy by bromocriptin was 38 (58.46%) . Therapy by bromocriptin was applied ( 2.5 -7.5 mg daily three doses ) in 38 patients for three cycles as The patient needed with monitoring ovulation monthly. 30 patients had ovulation (78.95%), and 8 patients failed (21.05%). The number of therapeutic cycles by bromocriptin was 77 cycles. Side effects of bromocriptin were : orthostatic hypotension 8 patients (12.05%), nausae 7 patients (18.42%), vomiting 5 patients (13.16%), headache 4 patients (10.53%), gastric pain 6 patients (15.59%).